Mitochondrial DNA (mtDNA) mutations in patients with suspected myoclonic epilepsy and ragged red muscle fibres (MERRF), Leigh syndrome (LS), and mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) - Olckers, Antonel (University of Pretoria, 2013)
Dissertation (MSc (Human Genetics))--University of Pretoria, 2007.